Designing EdTech tools using a codesign model: a multi-stakeholder design case - Mavri, Aekaterini; Ioannou, Andri; Kitsis, Andreas (My University, 2025)
This work presents a model to support the process of learning experience design (LXD) for educational technology. The model was developed and applied in the design of a self-reflection tool for 21st-century skills in maker education. Grounded in LXD, it integrates procedural and methodological perspectives from codesign and user experience (UX) design, by mapping three codesign dimensions - Staging, Negotiation, and Reframing–onto four UX phases - Analyse, Design, Prototype, and Evaluate. Enacted through an agile process involving 29 designers across four European countries, the model structured the collaborative activity across phases, dimensions, roles and objects. It offered the necessary clarity and practical scaffolding required in navigating complex, multistakeholder, multicultural and multidisciplinary initiatives. Key findings highlight process transparency, particularly between the preparatory and reflective dimensions that precede and follow the main design negotiations, designer role fluidity, inclusive participation, and the evolving role of design objects. The work offers a structured and transferrable approach to EdTech design at the intersection of LXD, UX, and codesign.
Keywords: EdTech (Educational Technology); codesign; learning experience design (LXD); maker education; learning design (LD); design case